(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper presents the design of 6-Tap FIR filter using Matlab simulink and Xilinx system generator for removal of noise from input signal. The implemented structure of 6 tap FIR filter uses the input signal with 48 Hz of frequency including noise. We designed structure uses sampling frequency of 100 Hz with oversampling concept, passband frequency of 0.31 Hz while the stopband frequency is of 2 KHz. This is a single rate FIR filter structure for 6 tap. The main objective of this designed filter is to reduce the noise from given signal. This Filter is designed using the FDA tool with 1 dB passband attenuation & 60 dB stopband Attenuation.